Anesthesia management in living-donor liver transplantation in a patient with carbamoyl phosphate synthetase deficiency: a case report - Hiroki Matsushita; Tetsushiro Fujiyoshi; Koichiro Yoshimaru; Toshiharu Matsuura; Yuichi Mushimoto; Yuji Karashima; Ken Yamaura (JA Clinical Reports, 2022)
Abstract Background Carbamoyl phosphate synthetase deficiency (CPS1D) is a urea-cycle disorder (UCD). We report successful perioperative management of pediatric living donor liver transplantation (LDLT) in a CPS1D patient. Case presentation A 10-year-old female patient with CPS1D underwent LDLT. Proper administration of dextrose 50% and 60 kcal/kg/day with l-arginine and l-carnitine resulted in the avoidance of intraoperative hyperammonemia induced by hypercatabolism. Serum ammonia level transiently increased to 61 mmol/L in the anhepatic phase and decreased to 44 mmol/L after reperfusion. Conclusions We suggest anesthesia management with administration of dextrose to avoid hyperammonemia during LDLT in patients with CPS1D.